ANALYSIS OF COARSE AGGREGATE CONTENT FROM RECLAIMED ASPHALT PAVEMENT OF WARM MIX ASPHALTIC CONCRETE BINDER COURSES (AC-BC) ON RESILIENT MODULUS AND FATIGUE TEST - Fitry Hardhiyanti, Wulan
The use of pavement recycling technology or Reclaimed Asphalt Pavement (RAP) is one of the innovations in reducing on new materials in the construction of new roads and on road maintenance. RAP components consist of asphalt and aggregate. Aggregate in RAP material has undergone physical changes and the size has become smoother as the RAP material has received traffic loads. Improvements to the increase in the addition of coarse aggregate material are needed in the gradation of RAP material so that specifications can be achieved. Asphalt in RAP material has also been oxidized while serving traffic so that the asphalt becomes harder. RAP asphalt requires to restore asphalt properties, that is using a rejuvenator. The warm RAP mixture and the material have something in common, namely that they require improvement by reducing asphalt viscosity. Evotherm additive is used as an asphalt softener as a warm mixture and as a rejuvenator in RAP asphalt. The RAP materials were obtained from three different locations, those are Cikampek Toll Road, Purbaleunyi Toll Road, and Tangerang-Merak Toll Road. The RAP mixture used was WMA AC-BC at the proportion of 30% RAP material, 70% of addition of new material and rejuvenators. The performance of the WMA-RAP affect is known by empirical testing, that is Marshall, mechanistic testing that is Resilient Modulus by UMATTA and fatigue resistance test by four points loading control strain method. The most addition of coarse material proportions was carried out on the A2 34.92%, the A1 mixture 7.41% and the A3 mixture 6.18%. In the use of RAP material, a WMA-RAP with the addition of a small amount of coarse material has a better performance (A1,3) compared to a mixture that requires improvement in gradation with the addition of more coarse aggregate (A2). This is indicated by the fulfillment of the stiffness by empirically and mechanistically. On fatigue test, it was found that the A1, A3 mixture had a fatigue life that was not much different from the A0 control mixture.